Successful agricultural mechanisation in sub-Saharan Africa and the significance of agricultural financing - Corinna Müller; Christiane Ströh de Martínez; Michael Brüntrup (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The majority of the population in sub-Saharan Africa (SSA) lives in rural areas and is directly or indirectly dependent on agriculture. As land is usually tilled by smallholders manually with a hand hoe, or mattock, the worker's output and productivity (and with it, their income) is low, and the actual workload high. Similar conditions apply in downstream sectors, ranging from processing and transport to marketing. This frequently results in negative health implications for the workers, many of them women, and makes the agricultural sector less appealing. Particularly in the event that they have achieved good levels of schooling or training, young people prefer to take up employment in the cities and choose to leave rural areas. In addition to the heavy workload, further consequences of manual cultivation include high harvest and post-harvest losses, lack of competitiveness, low agricultural exports and high imports. Agricultural mechanisation can help to improve this situation. Its significance is demonstrated in the declaration contained in the African Union's “Agenda 2063: The Africa We Want” to abolish the mattock by 2025. This is at the very core of a more systematic agricultural modernisation strategy. If implemented sensibly and gradually for particularly appropriate processes and in the case of labour shortages, a frequent criticism associated with this approach, namely that mechanisation causes job losses, does not necessarily apply. Indeed, the job ratio created via mechanisation can be thoroughly positive. However, a number of aspects must be taken into account in order to ensure agricultural mechanisation is successful: Not every viable stage of mechanisation makes economic sense for all small enterprises. That said, alternative exploitation models (machinery rings, larger agricultural enterprises, specialist service enterprises, contract cultivation) and appropriate technologies (e.g. two-wheel tractors) may make mechanisation accessible to these as well. Additional cultivation and marketing measures are often required. The fast and reliable provision of spare parts, repair services, operating materials and fuel or energy must be guaranteed. Specific financial products, including combined loans for customers and suppliers, savings and loan products and leasing models can make mechanisation more accessible. Mechanisation processes should be promoted in a market-driven manner; the state's role should be limited to supportive measures. In the process, subsidies should be “smart”, i.e. not cause market distortion, of limited duration and conducive to the economic sustainability of the stakeholders and systems involved. Along the value chains, professional competence should be boosted via training courses, either via the private or public sector. The financial and agricultural sectors must collaborate to find solutions for specific mechanisation requirements, and receive support in this joint endeavour.
Keywords: 330; Landwirtschaft und ländliche Entwicklung; Agriculture and rural development